What's on your hard drive?. - O'Hanlon, Charlene (New York ACM, 2006)
Ahhhh, April. A time to break free from winter's grasp and begin anew. So along with those parkas and snow blowers, why not pack away some of your less-than-satisfactory dev tools and take a look at this month's WOYHD. You might just read about the cool new tool you've been waiting for. While you're at it, stop by http://www.acmqueue.com and send us your rants and raves. If we accept your submission, you'll win a shiny new Queue coffee mug. What better way to start your spring?
Keywords: Computing Milieux; Personal computing; Miscellaneous; Management/Maintenance.